The INFORMATION SYSTEM WEB-BASED ACCEPTANCE OF NEW STUDENTS (CASE STUDY: SMK N KARTOHARJO MAGETAN): web-based acceptance of new students - Fatkhur Rokhman (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
The development of information technology today cannot be separated from all human activities, information technology also affects the field of education. In this case, the Admission of New Students at SMKN Kartoharjo Magetan still applies a manual registration system, namely by coming directly to the school to get a registration form from the school. To solve the problem above, an application was made entitled "Web-Based New Student Admission Information System (Case Study of SMKN Kartoharjo Magetan)". This study uses the waterfall development research method. The modeling used is a Unified Modeling Language with diagrams used use case diagrams, activity diagrams, sequence diagrams. This new admissions information system was built using the PHP programming language and utilizes the MySQL database as a database server. The test results from the New Student Admission Information System get results that are in line with expectations with the Blackbox Testing test. So it can be concluded that the accurate percentage of system success is 100%.